2021
DOI: 10.1101/2021.03.09.21253241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 mRNA Vaccination in Lactation: Assessment of adverse events and vaccine related antibodies in mother-infant dyads

Abstract: Importance: Data regarding efficacy and safety of anti-COVID-19 mRNA vaccines during lactation is needed to address vaccination guidelines, ease vaccine hesitancy concerns, and inform public health strategies for this population. Objective: To determine whether anti-COVID-19 mRNA-based vaccines administered during lactation illicit an immune response or the transfer of anti-SARS-CoV2 antibodies into human milk. Design: Plasma and milk samples were collected from a prospective cohort of lactating individuals w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Our detected milk SIgA prevalence is on the lower-end of the interval of milk IgA prevalence (61.8% to >80%) detected by others [16][17][18][19][20] . This discrepancy can probably be ascribed to different experimental procedures.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our detected milk SIgA prevalence is on the lower-end of the interval of milk IgA prevalence (61.8% to >80%) detected by others [16][17][18][19][20] . This discrepancy can probably be ascribed to different experimental procedures.…”
Section: Discussionsupporting
confidence: 51%
“…Importantly, neutralizing SIgA antibodies elicited through maternal vaccination protect suckling infants from respiratory disease upon transfer via breastmilk 15 . Few recent reports have documented IgA presence in the breastmilk in response to COVID-19 mRNA vaccines [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation is present not only in studies of mothers who have passed the infection, but also in those in which the breast milk of mothers vaccinated against SARS-CoV-2 has been analysed, and it is also mentioned that additional studies are needed to evaluate the effect of these vaccines on lactation outcomes and infant health because the protection they may provide to the child has not been studied [ 82 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same has been shown for mothers vaccinated with the mRNA vaccine technology, where SARS-CoV-2-specific IgG and IgA antibodies seem to appear in breastmilk soon after the first dose and reach maximum levels about 2 weeks after the second dose (Kelly et al, 2021; Pace et al, 2021; Perl et al, 2021). A number of pre-prints have also shown that even though both IgA and IgG antibodies appear in milk after vaccination, IgG seems to be the prominent isotype reported in the majority of studies but results are still inconclusive (Baird et al, 2021; Bertrand et al, 2021; Esteve-Palau et al, 2021; Fox et al, 2021; Friedman et al, 2021; Golan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%